Entre o escuro e a rutilância: As armadilhas de Eros e Tanatos em duas narrativas de Hilda Hilst. - Rodrigues, Ivon Rabelo (2010)
The short stories Lucas, Naim (1977) and Rútilo NADA (1993), written by Hilda Hilst (1930-2004) are placed side by side in order to articulate a set of glaring evidence of a distinction which violates common sense. In these texts, mature men fall in love for younger men and they accept humiliation and brutal death the price paid for refusing the moral up. We seek to think about the ego's reaction to the denial of passion and the consequent acceptance of self-destructive instincts and how does it affects the behavior of the characters, focusing on how psychoanalysis theoretically cut the death instincts. This approach considers all human behavior motivated by escape from pain and the pursuit of pleasure. Sigmund Freud (1856-1939) argued that this relationship is influenced by innate energy that overwhelm the body to a discharge, describing them as two antagonistic: the instinct of a sexual nature with a tendency to preservation of life (Eros) and its antagonist (Thanatos), a instinct that leads to the segregation of all that is alive. Both never act in isolation, because they are always working together. This research enabled us to know the author s mechanisms that rework and update the concept of life instinct symmetry in the destructive instinct. Through a procedural line of comparative perspective, using theoretical assumptions that reveal and prioritize the textuality, it became evident relations discourse about the events of Death and Love as thematic elements of the texts approximated. The scope of our contribution in this procedure is the major premise of intratextuality: how we developed certain themes that are unfold in Lucas, Naim and reconfigured in Rútilo NADA.